Hydrothermal Synthesis and Performance of Li 4 Ti 5 O 12 and Sn Composite as Anode Material for Lithium Ion Battery - Widhiatmaka Widhiatmaka; Guntur Tri Setiadanu (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Lithium titanate (Li4Ti5O12) and tin (Sn) composites are successfully prepared by hydrothermal synthesis. The objectives of this research were to obtain a spinel structure of LTO at a calcination temperature of 500C, and to improve performance of LTO by addition of Sn. The thermal, crystal structure, microstructure and electrical properties of the samples have been characterized by DT/TGA, XRD, SEM/EDX, and EIS, respectively. Meanwhile, electrochemical properties were analyzed using a charge-discharge battery analyzer. The results showed that the spinel phase was obtained for LTO 500oC and 10%Sn composite with the highest conductivity value of 9.06 x 10-7 S/cm. Cyclic voltammetry test showed a couple of anodic-cathodic reduction-oxidation (redox) voltages at 1.48V and 1.74 V for LTO and at 1.65 V and 2.11 V for TiO2. Lithiation voltage for Sn occurred at 0.61 V. The charge/discharge test of LTO 500oC and 10%Sn composite showed that the addition of Sn exhibited capacity at low current-voltage (0.6 V), identifying the advantages of composite which still had discharge capacity at low voltage. The specific capacity for LTO 500oC and 10%Sn composite increased from 76 to 110 mAh/g at 0.3C rate. And the spinel LTO sample can work up to 60C rate.